Transforming economics : perspectives on the critical realist project - Lewis, Paul, 1971- (London ; New York : Routledge, 2004)
This book is on the heterodox sections of economics,and in particular upon criticl realist approaches to the subject.Also the impact and usefulness of critical realism in relation to the different spheres within economics.
Includes bibliographical references and index.
aia 24/09/13
Loan
Keywords: Economics -- Methodology; Critical realism